Study on the energy evolution process and damage constitutive model of concrete–granite composite specimens under uniaxial compression load - Zhuo Dong; Yingxian Lang; Bin Gong; Ruifu Yuan; Zhengzhao Liang; Shanyong Wang; Chun’an Tang (Geomechanics and Geophysics for Geo-Energy and Geo-Resources)
Abstract The interaction between concrete structures and rock foundations is a crucial research topic for assessing safety and stability in geotechnical and underground engineering. The uniaxial compression tests were conducted on different combination modes (concrete component heights (H c), interface inclination angle (β), and coarse aggregate contents) to investigate their impact on the mechanical and energy response of concrete–granite composite specimens (CGCSs). This study categorized three failure modes: only concrete component failure (H c = 80 mm), shear failure along the interface (β = 30°), and simultaneous failure of both components (other combination modes). The fractal dimension (D f) of surface cracks positively correlates with H c, while the compressive strength (σ CGCS) and stiffness (E CGCS) exhibit an inverse trend. The value of D f and σ CGCS both exhibit a ''U-shaped'' trend when β ranges from 0° to 90°, whereas the value of E CGCS decreases linearly. Moreover, The value of D f and E CGCS positively correlate with coarse aggregate contents, while the value of σ CGCS trends vary non-monotonically increases. The coarse aggregate contents have few effects on energy conversion. Typical brittle failure (β = 0°, β = 30°, and H c = 20 mm) and ductile failure (other combination modes) are observed. Energy evolution characteristics offer quantitative insight into the damage evolution processes of CGCSs. The piecewise damage constitutive model based on dissipation energy can accurately describe the mechanical response of CGCSs. This study enhances understanding of the mechanical properties, failure characteristics, and energy evolution process of CGCSs under complex combination modes.